Bilobalide promotes expression of glial cell line-derived neurotrophic factor and vascular endothelial growth factor in rat astrocytes - Zheng Shi-Xi; Zhou Li-Jun; Chen Zhong-Liang; Yin Meng-Long; Zhu Xing-Zu (Acta Pharmacologica Sinica, 2016)
"AIM: To study the effects of bilobalide on the expression of glial cell line-derived neurotrophic factor (GDNF) and vascular endothelial growth factor (VEGF) in rat astrocytes in vitro. METHODS: Semiquantification polymerase chain reaction (SQ-PCR) was used to investigate GDNF and VEGF mRNA expression in the astrocytes after bilobalide (5, 15, 50, 100 mumol.L-1) treatment. Immunohistochemistry method was used to detect GDNF and VEGF protein expression in cells treated with bilobalide 50 mumol.L-1 for 24 h. RESULTS: GDNF and VEGF mRNA increased markedly after astrocytes were treated with bilobalide 50 mumol.L-1 for 12 h. GDNF and VEGF protein were detected in the cytoplasm of astrocytes after the cells were treated with bilobalide 50 mumol.L-1 for 24 h. CONCLUSION: Bilobalide induced GDNF and VEGF expression in the cultured astrocytes."